Mandibular First Molar with a Single Root and Single Canal - Chandrasekaran Sooriaprakas; Suma Ballal; Natanasabapathy Velmurugan (Hindawi Limited, 2014)
Successful endodontic management of mandibular first molar with a single root and single canal is diagnosed with the aid of dental operating microscope and multiple angled radiographs. In addition all the mandibular molars and premolars were single rooted on either side.